2018
DOI: 10.1155/2018/9789370
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Properties of Vanadium Oxide Thin Films by Plasma-Immersion Ion Implantation

Abstract: The paper describes the effect of doping with hydrogen and tungsten by means of plasma-immersion ion implantation (PIII) on the properties of vanadium dioxide and hydrated vanadium pentoxide films. It is shown that the parameters of the metal-insulator phase transition in VO 2 thin films depend on the hydrogen implantation dose. Next, we explore the effect of PIII on composition, optical properties, and the internal electrochromic effect (IECE) in V 2 O 5 ⋅nH 2 O films. The variations in the composition and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…The implantation of hydrogen into the VO 2 films was carried out in the PIII setup described in [12] under the following conditions the discharge current was 9.5 A, discharge voltage -65.9 V, cathode heating current -65 A, pressure -4 Pa, and the gas flow was 0.0018…”
Section: Experimental Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The implantation of hydrogen into the VO 2 films was carried out in the PIII setup described in [12] under the following conditions the discharge current was 9.5 A, discharge voltage -65.9 V, cathode heating current -65 A, pressure -4 Pa, and the gas flow was 0.0018…”
Section: Experimental Methodsmentioning
confidence: 99%
“…One of the effective ways to change the transition parameters and study its physical mechanism is doping with various elements, including hydrogen [3][4][5][6][7][8][9][10]. Previously we have reported [11,12] on the change in the properties of vanadium dioxide films and in the MIT parameters at hydrogenation by the method of plasma-immersion ion implantation (PIII). It has been found that the introduction of hydrogen by the PIII method into vanadium dioxide films with a relatively low hydrogen concentration (less than 10 at.%) leads to a decrease in the conductivity jump, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations